Genome sequence of Vibrio sp. SALL 6 isolated from shellfish - Vengadesh Letchumanan; Hooi-Leng Ser; Wen-Si Tan; Kok-Gan Chan; Nurul-Syakima Ab Mutalib (Progress in Microbes and Molecular Biology)
Members of the Vibrionaceae family are well known as foodborne pathogen that cause hazard to human in many forms of clinical infection and also affecting aquaculture via infection to livestock. This pathogen has caused seafood associated gastroenteritis cases in many countries including United States, Asian, and South East Asian countries. Antibiotics are usually used as prophylactic and therapeutic to manage the rising Vibrio infections, however, this in turn led to emergence of antibiotic resistant strains in the environments. Vibrio sp. SALL 6 isolated from shellfish was selected for genome sequencing to further explore its antimicrobial traits. Here, a high-quality genome sequence of Vibrio sp. SALL 6 is reported, while its genome reveals a potential for future antibiotic resistance managements.